State of fear - Michael Crichton (HarperCollins Publishers, 2004)
This novel is another thriller from the bestselling author of 'Jurassic Park' and 'Prey'. Drawing on his past as a Harvard Medical School student and his ongoing study of the world of technology, Crichton's gripping fiction is grounded in scientific fact culled from the latest academic journals.